PENGARUH VARIASI SUHU TERHADAP KEKUATAN MEKANIKA PADA ALUMUNIUM 7075-T6 DENGAN METODE ELEKTROPLATING - Hardinus Apriantoni; Gaguk Marausna; Ferry Setiawan (Sekolah Tinggi Teknologi Kedirgantaraan, 2023)
Aluminum alloy 7075 series is one that is widely used in the aviation industry. More than 73% of aircraft components are aluminum alloy 7075 series because the properties of this aluminum can still be improved by giving it a treatment. The purpose of this study was to determine the effect of differences in nickel coating types on 7075-T6 aluminum plates on the level of hardness.aluminum plates with a length of 2 cm and a width of 2 cm as many as each variation of 4 specimens. temperature variations of 30 °C, 35 °C, 40 °C, 45 °C and time of 5, 10, 15, 20 minutes. The hardness value is obtained using a brinell test device, using a diamond pyramid indenter used for vickers hardness tests. The test object is pressed for 5 seconds with a load of 31.25 kgf and a magnification of 5 times. Hardness testing is carried out at 1 point of the surface of the specimen. Based on the results of research and calculations and discussions about the effect of temperature variations on the strength of mechanics by the electroplating method, it is known that the difference in time and temperature variations on the hardness of aluminum 7075-T6 shows an influence on the value of significant hardness. And the optimal variation value was obtained, namely the highest hardness value at a temperature of 45 ° C at a time of 5 minutes, namely 483.63 kgf / mm² and the lowest average hardness value at a temperature of 30 ° C at a 15-minute immersion time of 292.33 kgf / mm².